Spoken and written discours: A multi-disciplinary perspective - Johandarie, Khosrow (Stamford Ablex publishing Corporation, 1999)
This volume presents a systematic, reasonably exhaustive, and critical view of the existing scientific literature on the differences between speech and writing and, particularly, the cognitive and cultural implications of these differences. It is unique in its multidisciplinary scope and analytical depth as it brings together, for the first time, this multiplicity of theory and evidence from varied disciplines.